2020
DOI: 10.33899/ijvs.2019.125633.1116
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of heat shock protein 70 gene in Iraqi buffalo

Abstract: The heat shock protein 70 (HSP 70) has important roles in protecting cells and keeping them alive when exposed to different stress conditions. The polymorphism of the hsp 70 gene could be linked with the ability of stress tolerance. This study aimed to determine the polymorphism of the hsp 70 gene in Iraqi buffaloes and study bits effects on the resistance to stress. This study was conducted during from November 2018 to February 2019. The number of buffalo females used was 35 at the age of 4-6 years, which bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Interestingly, Sosa et al (17) reported three nucleotide substitutions in GnRHR gene associated with ovarian inactivity in Egyptian buffaloes. So the genetic variation is needed for buffalo selection (34).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Sosa et al (17) reported three nucleotide substitutions in GnRHR gene associated with ovarian inactivity in Egyptian buffaloes. So the genetic variation is needed for buffalo selection (34).…”
Section: Discussionmentioning
confidence: 99%
“…The HSP70 protein, an important member of HSP family, is used as a significant indicator and molecular marker of adaptation to harsh environmental stress, since it is the most excitable protein against environmental stress among all HSPs. This protein has a variety of functions, such as resistance to stress and disease, protecting living cells and ensuring their survival (Patir and Upadhyay, 2010;Habib, 2020). In addition, the HSP70 protein is used as a selection parameter in developing of heat stress resistant breeds in cattle.…”
Section: Heat Tolerance and Genesmentioning
confidence: 99%
“…In goats, the gene coding for the HSP70 protein comprises 1926bp nucleotide sequences corresponding with 641 amino acids and is located on chromosome 23 (Gade et al, 2010). Although HSP70 genes are highly conserved molecules (Pawar et al, 2013), several studies suggest the possibility of genetic polymorphisms of the HSP70 gene [Fatima et al (2019) and Nikbin et al (2014) in goat; Habib et al (2017) in bulls; Habib et al (2018a) in rams; Habib (2020) in buffaloes and Habib et al (2020) in poultry]. Iraqi local goats generally suffer from many problems directly affecting their production.…”
Section: /9mentioning
confidence: 99%